Crowning Moments: Transformative populist use of the media and the case of Carl I. Hagen - Mjelde Hilmar (Nordicom Review, 2019)
This article presents the concept of a “crowning moment” and proposes an explanation for the media-savviness of many populist leaders – an under-theorised ability often referred to in existing research. A crowning moment is an instance in which populist leaders take advantage of opportunities that arise in their surroundings to achieve a or multiple major policy, political and/or personal goals through skilful use of the media that earns them recognition as savvy politicians. The concept is exemplified through an analysis of Norwegian Progress Party leader Carl I. Hagen’s role in the 1987 no-confidence motion against the Labour Party government. Stoking up and exploiting media interest in dramatic fashion, Hagen managed to redefine himself as a national political leader and made his party appear responsible.